Radial Growth of Trees Rather Than Shrubs in Boreal Forests Is Inhibited by Drought - Yang, Jingwen; Zhang, Qiuliang; Song, Wenqi; Zhang, Xu; Wang, Xiaochun (Frontiers in Plant Science, 2022)
Of all forest biomes, boreal forests are experiencing the most significant warming. Drought caused by warming has a dramatic impact on species in boreal forests. However, little is known about whether the growth of trees and shrubs in boreal forests responds consistently to warming and drought. We obtained the tree-ring width data of 308 trees (Larix gmelinii and Pinus sylvestris var. mongolica) and 133 shrubs (Pinus pumila) from 26 sites in northeastern China. According to the climate data from 1950 to 2014, we determined three extreme drought years (1954, 1967, and 2008). The response difference of radial growth of trees and shrubs in boreal forests to drought was compared using resilience index, moving correlation and response analysis. The results showed that high temperature (mean and maximum temperature) in previous and current growing seasons promoted the growth of P. pumila, but inhibited the growth of trees. On the contrary, wetter conditions (higher PDSI) promoted tree growth but were not conducive to P. pumila growth in high latitudes. Moving correlation analysis showed similar results. In addition, water deficit was more likely to inhibit P. pumila growth in low latitudes. The drought resistance of P. pumila was stronger than that of L. gmelinii and P. sylvestris var. mongolica. Therefore, the growth loss and recovery time of P. pumila during drought was less than those of trees. We concluded that L. gmelinii and P. sylvestris var. mongolica are more prone to growth decline than P. pumila after the drought caused by climate warming. In the future climate warming, shrub growth may benefit more than trees. Our findings are of great significance in predicting the future changes in ecosystem composition and species distribution dynamics in extreme climate susceptible areas.